2002
DOI: 10.1152/ajpcell.00437.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase-dependent, MEK- independent proliferation in response to CaR activation

Abstract: .-Although ovarian surface epithelial (OSE) cells are responsible for the majority of ovarian tumors, we know relatively little about the pathway(s) that is responsible for regulating their proliferation. We found that phosphatidylinositol 3-kinase (PI3K) is activated in OSE cells in response to elevated extracellular calcium, and the PI3K inhibitors wortmannin and LY-294002 inhibited extracellular signalregulated kinase (ERK) activation by ϳ75%, similar to effects of the mitogen-activated protein kinase/ERK k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Our observation that the ERK/MAP kinase pathway is important for the induction of OSE cell growth is supported by previous studies using the MEK inhibitor PD98059 (Bilderback et al 2002). The data presented here is also consistent with a previous report demonstrating the role of ERK in HGF-induced human OSE cell growth and further demonstrates that IGF-I and hCG also induce OSE cell growth via the ERK pathway.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observation that the ERK/MAP kinase pathway is important for the induction of OSE cell growth is supported by previous studies using the MEK inhibitor PD98059 (Bilderback et al 2002). The data presented here is also consistent with a previous report demonstrating the role of ERK in HGF-induced human OSE cell growth and further demonstrates that IGF-I and hCG also induce OSE cell growth via the ERK pathway.…”
Section: Discussionsupporting
confidence: 93%
“…The data presented here is also consistent with a previous report demonstrating the role of ERK in HGF-induced human OSE cell growth and further demonstrates that IGF-I and hCG also induce OSE cell growth via the ERK pathway. Other signalling pathways that are important to maintain OSE cell growth and/or survival include the Akt/ phosphoinositide 3-kinase pathway (Bilderback et al 2002); stimulation of the Akt/phosphoinositide 3-kinase pathway by IGF-I, under the control of hCG, induces cell survival (Kuroda et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium levels are important for signalling and growth in OSE cells, with increased proliferation being seen in response to elevated calcium in vitro (McNeil et al 1998, Hobson et al 2000, Bilderback et al 2002, Wright et al 2002. This effect has been shown to be mediated by ERK1/2 (Hobson et al 2000), PI3K Endocrine-Related Cancer (2010) 17 335-349 www.endocrinology-journals.org (Bilderback et al 2002) and the calcium-sensing receptor CaR (Hobson et al 2003). We have shown that FSH-and LH-induced ERK1/2 activation in EOC cell lines is dependent on both extra-and intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on cell-specific coupling to appropriate G-proteins, activation of the CaR by elevated extracellular Ca 2 þ reduces the rate of cellular proliferation, as seen in human colon carcinoma (Kallay et al, 2003;Chakrabarty et al, 2005) or ovarian surface epithelial cells (Bilderback et al, 2002), but may also stimulate cell growth, as seen in malignant Leydig cells , and protect from apoptosis, for example, in prostate cancer cells (Lin et al, 1998).…”
Section: Cancermentioning
confidence: 99%